THE FLUENCY OF MASS MEDIA ON SOCIETY - Ahmedov , Azimjon Ilhomovich; Sayfiddinova , Gulnoza (Educational Research in Universal Sciences, 2023)
Technological revolution of 20 the century, mass media affects behaviour of people in society, parents and their child’s exposure to media.